Le réchauffement climatique va-t-il conduire les petites îles à être englouties sous les invasions biologiques ? - Jacques Tassin (VertigO)
One of the main consequences expected from climate change is an increasing amount of biological invasions, which can benefit from ecological niches released by native species. Within small islands, such an effect might be enforced by (i) a strong introduction pressure which will be probably strengthened by the research of well-adapted living products, (ii) the low species richness within native communities, (iii) the risk of extinction resulting from tiny ecological gradients. The aim of the paper is too provide an illustrated framework, detailing the ecological changes which are expected within small islands, in a prevailing context of climate change. The change in ecological niches will result in modifications observed at the respective levels of (i) the composition of species communities, (ii) the functioning of biotopes, (iii) but also the production of goods and ecosystemic services. Yet, the ex ante evaluation of the consequences of climate change on biological invasions argues for considering both negative and positive impacts. Such an analysis reveals that in some cases, invasive species can provide functional compensations resulting from the extinction of native species, and that they can even increase the production of goods and ecological services.